Extraction, structural characterization, and in vitro immunomodulatory activities of Saccharomyces cerevisiae spore wall β-glucan - Mengqing Yan; Xue Wang; Jingtao Zhang; Shuheng Yang; Cong Pan; Shiwei Liu; Jia Liu; Youqiang Yu; Fangli Ding; Shenglin Duan; Huoqing Huang; Guoyu Liu; et al. (Journal of Agriculture and Food Research)
Saccharomyces cerevisiae spores exposing β-glucan layers exhibit notable immunomodulatory properties, suggesting their potential as a natural and efficient source of β-glucans. However, studies on the application of spore wall β-glucans are limited, and their precise structural characteristics and immunological mechanisms remain poorly understood. This study aimed to investigate the structural characteristics and immunomodulatory properties of β-glucan extracted from the yeast spores (YSG) and compare them with those of β-glucan derived from vegetative cells (YG). Similar to YG, YSG consists of a backbone chain of β-(1,3) glucan and side chains of β-(1,6) glucan with a natural triplex structure. However, there are differences in the branching ratio and helical structure between YSG and YG. YSG has fewer branches and a less pronounced triple helix structure than YG. The particle size (222.4 nm) and molecular weight (Mw: 1392.27 kDa) of YSG were found to be significantly smaller than those of YG. Additionally, YSG can bind to the Dectin-1 receptor protein on the surface of macrophages, activating the Syk/CARD9/NF-κB pathway to promote the expression of iNOS and cytokine mRNAs, thereby facilitating the release of NO and related cytokines for increased immunostimulatory effects. Collectively, our results provide foundational insights into the potential of yeast spore wall β-glucan as a functional immunostimulatory agent.